Simulink model of transformer differential protection using phase angle difference based algorithm - Nassim A. Iqteit; Khalid Yahya (Institute of Advanced Engineering and Science, 2020)
An application of phase-angle-difference based algorithm with percentage differential relays is presented in this paper. In the situation where the transformer differential relay is under magnetizing inrush current, the algorithm will be utilized to block the process. In this study, the technique is modeled and implemented using Simulink integrated with MATLAB. The real circuit model of power transformer and current transformers are considered in the simulation model. The results confirmed the effectiveness of the technique in different operation modes; such as, magnetizing inrush currents, current transformers saturation and internal transformer faults.